Effects of Blended Enzymes, Organic Catalysts, and Probiotics on the Water Quality of Pasig River, Philippines - Gladys B. Magdaraog; Listya Purnamasari; Joseph P. Olarve; Joseph F. dela Cruz (Indonesian Journal of Social and Environmental Issues (IJSEI), 2022)
The study was conducted to evaluate the effectiveness of the blend of enzymes, organic catalysts, and probiotics on the water quality of Pasig River and to determine its sustainability to aquatic life. The effects of varying the dosage of the mixture were also identified. The data observed were compared to the standard for fishery water set by the Department of Environment and Natural Resources (DENR). On-site application results were analyzed using paired t-test. All parameters were normally distributed. Temperature, phosphate, and BOD measures were significantly changed at (p<0.05). Results showed mixture effectiveness on temperature, pH, Chloride, Nitrate, TSS, Oil and Grease, and Surfactant as they passed the DAO 2016-08 Class C Standard. BOD, Phosphate, TSS, and Ammonia concentrations were reduced in Ayala samples. DO, Nitrate and Fecal Coliforms concentrations were reduced in Nagtahan samples. Varying the amount of mixture application yields no significant effect on the water quality. Fishes and aquatic life can still not thrive on this kind of water.